2011
DOI: 10.1182/blood-2011-03-340232
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of a first thromboembolic event in asymptomatic carriers of high-risk antiphospholipid antibody profile: a multicenter prospective study

Abstract: Persistent antiphospholipid (aPL) antibodies are occasionally found in subjects without prior history of thromboembolic events (TEs), raising the dilemma of whether to initiate or not a primary thromboprophylaxis. A first TE is considered rare in aPL carriers, but previous studies did not consider the aPL profile nor was the test positivity confirmed in a reference laboratory. In this study, 104 subjects with high-risk aPL profile (positive lupus anticoagulant, anticardiolipin, and anti-␤ 2 -glycoprotein I ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
292
6
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 430 publications
(323 citation statements)
references
References 24 publications
11
292
6
14
Order By: Relevance
“…Abnormalities in coagulation and fi brinolysis pathways have been associated in the minority of CTEPH patients with most prevalent ones being LA and APA. Thrombophilia studies have shown that LA may be found in 10 % of CTEPH patients, and 20 % carry LA/APA or both (21,27,28). Contrary to other studies, LA/APA levels in our CTEPH patients were not increased.…”
Section: Tab 5 Triple Combination Of Cteph Risk Factorscontrasting
confidence: 99%
“…Abnormalities in coagulation and fi brinolysis pathways have been associated in the minority of CTEPH patients with most prevalent ones being LA and APA. Thrombophilia studies have shown that LA may be found in 10 % of CTEPH patients, and 20 % carry LA/APA or both (21,27,28). Contrary to other studies, LA/APA levels in our CTEPH patients were not increased.…”
Section: Tab 5 Triple Combination Of Cteph Risk Factorscontrasting
confidence: 99%
“…Recently, the term "aPL profile" has replaced the term "category" of positivity, and good evidence has been published regarding the high predictive role of the "triple" positivity aPL profile, consisting in the simultaneous, persistent positivity for LA, aCL and anti-beta2glycoprotein I. APS patients with triple positivity, as well as asymptomatic patients with triple positivity are at higher risk of thrombosis and thrombotic recurrences [9] and [10].…”
Section: Introductionmentioning
confidence: 99%
“…Investigators have raised uncertainty in the definite Indian J Hematol Blood Transfus (Jan-Mar 2017) 33 (1):8-14 9 diagnosis of APS on the basis of a single positive test. This is based on the lower incidence of first thromboembolic events in carriers with isolated LAC positivity compared to carriers with triple positivity (5.9 vs. 37 % at 10 years) [14,15]. The risk of thrombosis was higher in carriers of two or three aPL antibodies when compared with those with single positivity [16].…”
Section: Issues With the Current Diagnostic Criteria Of Aps And Propomentioning
confidence: 99%